Isolation of marine bacteria inhibitory to shrimp bacterial pathogens - Jayanth, K; Jeyasekaran, G; Shakila, R Jeya; Shanmugam, S A (Indian Journal of Fisheries, 2011)
Pigmented bacteria from seawater, sediment, seaweeds, bivalves and submerged substrates from Tuticorin coast were screened for the antagonistic activity. Of the 166 strains isolated, 15 showed inhibitory activity against shrimp bacterial pathogens. Alteromonas was the antagonistic marine bacteria and it exhibited a wide antibacterial spectrum against various shrimp bacterial pahtogens viz., Vibrio harvyi, V. fischeri and V. alginolyticus. One strain of Alteromonas (A6) showed greater antagonism against the shrimp bacterial pathogens. Results suggest that these antagonistic marine bacteria could be used as biocontrol agents in the shrimp culture systems